2020
DOI: 10.1021/acs.macromol.0c01268
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of the Temperature Dependence of Activation Volume in Glass-Forming Polymer Melts under Variable Pressure Conditions

Abstract: Motivated by empirical observations suggesting that changes in the activation volume ΔV # upon varying temperature (T), determined from the pressure (P) dependence of the segmental structural relaxation time τ α , might be related to changes in the extent of collective motion in glass-forming liquids, we investigate the temperature dependence of ΔV # and the extent of collective motion in a coarse-grained polymer melt using molecular dynamics simulation. After confirming the validity of the string model of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
96
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 28 publications
(104 citation statements)
references
References 100 publications
8
96
0
Order By: Relevance
“…[29,30] As our approach has successfully described the glass transition of glass-forming liquids having simple and complex structures in both experiments [7][8][9][14][15][16]26,34] and simulation [21] in the past, in future work, it will be possible to extend our theoretical framework to study more complex polymer glasses, such as those in the previous studies. [37,38]…”
Section: Discussionmentioning
confidence: 99%
“…[29,30] As our approach has successfully described the glass transition of glass-forming liquids having simple and complex structures in both experiments [7][8][9][14][15][16]26,34] and simulation [21] in the past, in future work, it will be possible to extend our theoretical framework to study more complex polymer glasses, such as those in the previous studies. [37,38]…”
Section: Discussionmentioning
confidence: 99%
“…[19,[46][47][48][49] Over the last few decades, the CG-MD approaches have been broadly applied to explore the influences of fundamental molecular parameters on the thermomechanical behaviors of polymers with different segmental/chain structures at bulk and confined states. [50][51][52][53] The semi-crystalline morphology of PE under uniaxial tension has been explored via CG-MD methods. It was shown that polymer chains tend to align in the deformation direction, where the large extension and orientation of the chains were found to affect the crystallization and facilitate the primary nucleation.…”
Section: Introductionmentioning
confidence: 99%
“…The activation volume monotonically grows with cooling and overall this variation is qualitatively consistent with prior experiments [30][31][32] and simulations. [31,33,34] Our activation volumes are the same order of magnitude as simulations in ref. [33,34].…”
Section: Resultsmentioning
confidence: 88%
“…[31,33,34] Our activation volumes are the same order of magnitude as simulations in ref. [33,34]. On one hand, we roughly observe two linearly decreasing trends of log 10 ΔV # occurring in ternidazole, glycerol, and probucol.…”
Section: Resultsmentioning
confidence: 88%